A Case of Myxedema Coma Presenting as a Brain Stem Infarct in a 74-Year-Old Korean Woman - Ahn, Ji Yun; Kwon, Hyuk-Sool; Ahn, Hee Chol; Sohn, You Dong (Journal of Korean medical science, 2010)
Myxedema coma is the extreme form of untreated hypothyroidism. In reality, few patients present comatose with severe myxedema. We describe a patient with myxedema coma which was initially misdiagnosed as a brain stem infarct. She presented to the hospital with alteration of the mental status, generalized edema, hypothermia, hypoventilation, and hypotension. Initially her brain stem reflexes were absent. After respiratory and circulatory support, her neurologic status was not improved soon. The diagnosis of myxedema coma was often missed or delayed due to various clinical findings and concomitant medical condition and precipitating factors. It is more difficult to diagnose when a patient has no medical history of hypothyroidism. A high index of clinical suspicion can make a timely diagnosis and initiate appropriate treatment. We report this case to alert clinicians considering diagnosis of myxedema coma in patients with severe decompensated metabolic state including mental change.